Country Partnership Framework for Bulgaria for the Period FY17-FY22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
This program document presents the World Bank Group (WBG) FY17-22 Country Partnership Framework (CPF) for Bulgaria. The timing of the new CPF follows the preparation of theSystematic Country Diagnostic (SCD) prepared in FY15, and informs the areas and objectives ofthe CPF in support of the WBG’s twin goals to reduce poverty and boost shared prosperity1 for the bottom forty percent of the population. The CPF proposes to focus WBG support in selective areas aligned with the SCD, in response to clear Government demand, supporting and complementing Bulgaria’s European Union agenda, and reflecting the WBG’s comparative advantage. In addition, the CPF applies two key principles for engagement, including: (i) realism, recognizing that the WBG plays a selective role and that it will contribute most effectively by being strategic and catalytic in supporting key elements of Bulgaria’s development agenda, and (ii) scalability, creating opportunities to engage in dialogue and analytical work that may create space for broader engagement in areas where there is potential for transformational impact, including IFC investments in private sector development. Government demand is focused primarily on the agenda to strengthen public institutions, notably in the financial and energy sectors. The WBG will complement that focus by investing its own resources to stay engaged in the inclusion agenda, which is critical to the WBG twin goals. CPF proposes to cover a six year period, with Progress Learning Reviews (PLRs) will facilitate a more proactive approach to monitoring results and ensure close alignment with the country-led strategy.